More fragmented, and yet more networked: Analysing the responses of two Local Authorities in England to the Coalition's 'self-improving school-led system' reforms (UCL Press, 2015)
This paper explores school reform in England under the Conservative-led Coalition government, elected in 2010, through a focus on the changing roles and status of Local Authorities (LAs). The Coalition's stated aim was the development of a 'self-improving, school-led' system in which LAs should become 'champions for children'. The paper draws on two locality case studies and a set of future scenarios and policy narratives to analyse the ways in which LAs and school leaders are responding to reform. The paper concludes that the Coalition focused its attention on structural reform, but that this placed an additional onus on leadership agency within local school systems to shape contextually appropriate solutions. The schools in the two areas studied appear to have become more fragmented and yet - paradoxically - more networked; however, they are not yet working in the 'deep partnerships' envisaged by Hargreaves (2010). This has meant that the LAs have needed to sustain their traditional roles (for example, in providing challenge and support to schools), whilst simultaneously evolving new ways of working (for example, providing 'bridging social capital'). These roles may sometimes be in tension, but are driven by different factors: LA-level accountability in the case of challenge and support, and reduced funding in the case of 'bridging social capital'. This suggests that the Coalition's conflicting policy narratives were in tension and that the notion of LAs as 'champions for children' requires review.